Climate change and its impact on fertility - Wani, Khursheed Ahmad; Naha, Nibedita, 1972- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2021)
"This book studies climate change as the planet's biggest threat affecting fertility of mammals across the globe through its potential effects on heat stress, food and water security, extreme weather events, vulnerable shelter and population migration. It highlights the important and timely issues and concerns to address the latest impact of climate change, and mitigation strategies for enhancing early embryo survival and uterine potential"--